The politics, geography, and economics of desalination: a critical review. (16th February 2015) - March, Hug
Abstract : In the light of the collapse of the hydraulic paradigm, the intensification of the impact of climate change on the water cycle and rising global demands, desalination is portrayed as the solution to 21st century water issues. Led by state‐led desalination programs, but also with a strong participation of the private sector, the emergence and development of desalination have been geographically uneven in the last decades. Desalination has its drawbacks, not only in terms of environmental sustainability, because of the intensification of the water‐energy nexus, but also due to distributional issues that surround the access to desalinated water. These drawbacks are reviewed in detail and exemplified with reference to the case of Spain. Eventually, this article discusses to what extent desalination constitutes a radical break with the old 20th century hydraulic paradigm and interrogates whether it risks repeating the same mistakes, thus becoming a maladaptive strategy to cope with 21st century global water issues. WIREs Water 2015, 2:231–243. doi: 10.1002/wat2.1073 This article is categorized under: Engineering Water > Planning Water Engineering Water > Sustainable Engineering of Water Human Water > Water Governance